Implementation of TQM in Islamic-Based Schools: A Literature Review - Kusriyanto Kusriyanto; Nur Wening (Maneggio, 2024)
The quality of Islamic education in Indonesia plays an important role in supporting the improvement of education quality nationally in order to produce quality human resources (HR). This qualitative research aims to determine the implementation of Total Quality Management (TQM) in Islamic-based schools. The research was conducted using qualitative research methods, especially Systemic Literature Review (SLR) using the results of previous research. Based on a literature review study, it was found that TQM can actually be implemented in the management of the Islamic education system. By: 1) The principle of customer focus and total involvement, namely: leadership and employee empowerment. 2) Leadership roles, education and training, support structures, communication, rewards and recognition, and measurement 3) Implementation of continuous improvement, meaning that quality is always improved and adapted to changing customer needs and desires.